Assessment of Preserved Ratio Impaired Spirometry (PRISm) Based on Different Definitions in the Early COPD Cohort - Dai C; Tang G; Yang H; Wu F; Deng Z; Zheng Y; Zhao N; Lu L; Wan Q; Wang Z; Peng J; Wu X; et al. (International Journal of COPD)
Cuiqiong Dai,1,* Gaoying Tang,1,* Huajing Yang,1,2,* Fan Wu,1,2 Zhishan Deng,1 Youlan Zheng,1 Ningning Zhao,1 Lifei Lu,1 Qi Wan,1 Zihui Wang,1 Jieqi Peng,1,2 Xiaohui Wu,1 Kunning Zhou,1 Guannan Cai,1 Shan Xiao,1 Xiang Wen,1 Changli Yang,3 Shengtang Chen,4 Shuqing Yu,5 Ruiting Sun,1 Yumin Zhou,1,2 Pixin Ran1,2 1State Key Laboratory of Respiratory Disease & National Clinical Research Center for Respiratory Disease & National Center for Respiratory Medicine & Guangzhou Institute of Respiratory Health, The First Affiliated Hospital of Guangzhou Medical University, Guangzhou, People’s Republic of China; 2Guangzhou National Laboratory, Guangzhou, People’s Republic of China; 3Department of Pulmonary Medicine, Wengyuan County People’s Hospital, Shaoguan, People’s Republic of China; 4Department of Radiology, Wengyuan County People’s Hospital, Shaoguan, People’s Republic of China; 5Department of Pulmonary Medicine, Lianping County People’s Hospital & Lianping County Second People’s Hospital, Heyuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pixin Ran, Email pxran@gzhmu.edu.cn Yumin Zhou, Email zhouyumin410@126.comBackground: Preserved ratio impaired spirometry (PRISm), which identifies a population at high risk for COPD, has drawn increasing attention. However, definitions for PRISm vary across studies, and researches comparing these definitions are limited.Objective: We aim to assess the agreement, the clinical features, and the prevalence of PRISm defined by restrictive spirometric pattern (RSP) method [that is forced vital capacity (FVC) method] versus forced expiratory volume in the first second (FEV1) method and by fixed values versus the lower limit of normal (LLN).Methods: All 1862 participants from the ECOPD study underwent questionnaire investigation, spirometry, biphasic CT, and impulse oscillometry. Participants were categorized into control and two targeted groups (RSP fixed and PRISm fixed excluding RSP fixed) based on FVC and FEV1 fixed definitions. Similar categorizations were conducted for RSP LLN versus PRISm LLN and PRISm fixed versus PRISm LLN. We assessed the agreement, the clinical features, and the prevalence of PRISm among these various definitions, repeating all analyses using Global Lung function Initiative (GLI) equation.Results: Significant overlap with merely moderate agreement (Kappa coefficient = 0.706, P value < 0.001) existed between RSP fixed and PRISm fixed definitions. Participants identified as PRISm by both definitions exhibited lower lung function, higher airway reactance, and increased airway resistance compared to the control group. Similar findings were observed in RSP LLN versus PRISm LLN and PRISm fixed versus PRISm LLN. Our sensitivity analysis verified the consistency of these results. Furthermore, the prevalence of PRISm varied from 2.0% to 12.5% depending on the definitions and predicted equations, with the Chinese equation, LLN definition in Chinese equation and fixed definition in GLI equation yielding higher prevalence rates.Conclusion: Our findings highlight concerns about the comparability of studies and the interchangeability of various definitions and reference equations for PRISm.Keywords: PRISm, definitions, clinical features, prevalence, reference equations